Combustion Performance and Physicochemical Characteristics of Sawdust-Based Bio-Charcoal Briquettes using Molasses Adhesive - Ichsan, Andi Chairil; Ningsih, Rima Vera; Rini, Dwi Sukma; Webliana, Kornelia (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Bio-charcoal briquettes are a promising alternative to fossil fuels, particularly when produced from biomass waste such as sawdust. This study investigates the effects of varying molasses adhesive concentrations (5%, 10%, and 15%) on the physical and chemical properties of bio-charcoal briquettes produced from sawdust. The briquettes were analyzed for density, moisture content, ash content, volatile matter, fixed carbon, and calorific value. Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) were also employed to examine surface morphology and functional groups. The results showed that increasing molasses concentration led to higher density, moisture content, and fixed carbon content, while reducing ash and volatile matter content. The 10% molasses concentration provided the highest calorific value (5,420 cal/g). The results of testing using SEM with a magnification of 2000x, featuring a particle size of 60 mesh, revealed the morphology of the briquette surface with a regular arrangement of cavities. FTIR analysis confirmed the presence of O-H, C-H, and C=O groups, which contribute to molecular bonding. All samples met the SNI 01-6235-2000 standard for wood charcoal briquettes. The addition of 1% potassium chlorate further improved ignition and combustion. The findings demonstrate that molasses, as a low-cost and eco-friendly binder, effectively enhances the quality and energy performance of bio-charcoal briquettes. This study supports the development of renewable energy technologies from underutilized wood waste, promoting sustainable energy solutions and environmental conservation. Keywords: bio-charcoal briquettes, calorific value, combustion performance, molasses adhesive, sawdust waste